Hitler's secret pirate fleet : the deadliest ships of World War II - Duffy, James P., 1941- (Praeger, 2001)
"They were the deadliest ships of World War II - nine German commerce raiders disguised as peaceful cargo ships, flying the flags of neutral and allied nations. In reality, these heavily armed warships roamed the world's oceans at will, like 20th-century pirates. They struck unsuspecting freighters and tankers out of the darkness of night or from behind a curtain of fog and mist. For almost three years they led the Royal Navy on a deadly chase from sea to sea, seeding Allied ports with hundreds of mines and, on one occasion, even bombarding a shore installation."--Jacket